Optimal allocation and sizing of DG in distribution system using evolutionary programming technique - Siti Rafidah, Abdul Rahim; Titik Khawa, Abdul Rahman; Ismail, Musirin; Syahrul Ashikin, Azmi; Zainuddin, Mat Isa; Omar, Aliman; Ismail, Daut, Prof. Dr. (Universiti Teknologi MARA (UiTM), 2011)
The 2nd International Power Engineering and Optimization Conference (PEOCO 2008), organized by Universiti Teknologi MARA Malaysia, 4th - 5th Jun 2008 at Grand Blue Wave Hotel, Shah Alam, Selangor, Malaysia.